Investigation on the Evolution of Shiga Toxin-Converting Phages Based on Whole Genome Sequencing - Zuppi, Michele; Tozzoli, Rosangela; Chiani, Paola; Quiros, Pablo; Martinez-Velazquez, Adan; Michelacci, Valeria; Muniesa, Maite; Morabito, Stefano (Frontiers in Microbiology, 2020)
Bacteriophages are pivotal elements in the dissemination of virulence genes. The main virulence determinants of Shiga Toxin producing E. coli, Shiga Toxins (Stx), are encoded by genes localized in the genome of lambdoid bacteriophages. Stx comprise two antigenically different types, Stx1 and Stx2, further divided into subtypes. Among these, certain Stx2 subtypes appear to be more commonly occurring in the most severe forms of the STEC disease, haemorrhagic colitis and haemolytic uremic syndrome. This study aimed at obtaining insights on the evolution of Stx2 bacteriophages, due to their relevance in public health, and we report here on the analysis of the genomic structure of Stx2 converting phages in relation with the known reservoir of the E. coli strains harbouring them. Stx2 converting phages conveying the genes encoding different stx2 subtypes have been isolated from STEC strains and their whole genomes have been sequenced, analysed and compared to those of other Stx2 phages available in the public domain. The phages’ regions containing the stx2 genes have been analysed in depth allowing to make inference on the possible mechanisms of selection and maintenance of certain Stx2 phages in the reservoir. The “stx regions” of different stx2 gene subtypes grouped into three different evolutionary lines in the comparative analysis, reflecting the frequency with which these subtypes are found in different animal niches, suggesting that the colonization of specific reservoir by STEC strains could be influenced by the Stx phage that they carry. Noteworthy, we could identify the presence of nanS-p gene exclusively in the “stx regions” of the phages identified in STEC strains commonly found in cattle. As a matter of fact, this gene encodes for an esterase capable of metabolizing sialic acids produced by submaxillary glands of bovines and present in great quantities in their gastrointestinal tract.